Essential Oil Profile of Vietnamese Callicarpa candicans (Burm. f.) Hochr - Thu Le, Vu Thi; Phuong Thao, Lai Phuong; Hong Minh, Pham Thi; Bich, Hoang Thi; Lam, Do Tien; Thu Thuy, Dinh Thi; Quan, Pham Minh; Long, Pham Quoc; Hung, Dao Viet; Toan, Tran Quoc; Vo, Thanh Sang; Pham Thi, Hai Ha (Asian Journal of Chemistry, 2020)
In this study, the essential oil profile of Callicarpa candicans (Burm. f.) Hochr was presented. Samples were collected from Vietnam and the oils were extracted from fresh leaves and dry leaves by hydrodistillation method. GC-MS data and retention indices were used to identify the chemical composition. The essential oil performance achieved 0.263% for fresh leaves and 1.503% for dry leaves. A total of 47 components were identified from fresh leaves oil and 39 constituents from dry leaves oil. Chemical compositions of the two essential oils were similar, with the major components being α-gurjunene, δ-cadinene, ε-caryophyllene (β-caryophyllene) and α-selinene.